Sex-dependent differences in patients treated with regular hemodialysis - Ljubica Mitev Prokopović; Miodrag Sokolović; Branimir Haviža Lilić; Miomir Prokopović (Биомедицинска истраживања, 2023)
Introduction: The aims of the study were to find out sex differences among patients starting regular hemodialysis (HD) in 2014 and to check whether these differences change over a five-year period. Methods: The retrospective five-year study included 35 patients (24 men; 11 women) starting HD in HD centers in Leskovac and Pirot in 2014. Demographic data, clinical data, laboratory findings, and medication used for examined patients were taken from medical records. Results: A comparison of patients of different sexes at the beginning of the study showed that women were significantly older (70.55 ± 13.27 vs. 58.88 ± 15.27 years), but diabetes and hypertension were more frequent causes of chronic kidney disease in men. Women had significantly lower body mass index and serum creatinine level than men in the first year of the study. During all five years, the HD adequacy index spKt/V was higher in women than in men, but the difference reached statistical significance only in the third year (1.4 ± 0.2 vs. 1.2 ± 0.2). Serum iPTH level was higher in women than in men in almost the entire study period. There was no significant sex difference in blood pressure, type of vascular access, number of HD hours per week, in the percentage of patients who used erythropoiesis-stimulating agents or phosphate binders. During the study period 10 (42.7%) men and five (45.5%) women died and the most frequent causes of death were cerebrovascular and cardiovascular diseases. Conclusion: The study revealed several differences between men and women on regular HD, but no treatment inequality was found.
Keywords: hemodialysis patients; sex differences; retrospective study